(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the updated NDC, Vietnam has allocated mitigation targets to energy, agriculture, industrial processes and product use (IPPU), land use, land use and forestry change (LULUCF) and waste in the period of 2021-2030. The establishment of a measurement, reporting and verification system (MRV) at national and sectoral levels is necessary to track the progress towards national and sectoral mitigation targets. However, at present very few studies on MRV indicators and remain fragmented. To meet that urgent need, this study was implemented to develop MRV indicators for mitigation actions to support the policy makers in tracking the NDC implementation. In this paper, a set of 85 MRV indicators divided into two categories: (i) 12 outcome indicators to track the national and sectoral mitigation targets, (ii) 72 progress indicators to track the implementation of mitigation options (including 40 for energy, 14 for agriculture, 7 for LULUCF, 4 for IPPU and 7 for waste) were developed based on relevant studies and expert consultation. The paper also tested the application of progress indicators in several mitigation options in the energy sector. The result showed that in energy sector, in 2014 the two mitigation options that have highest progress include: High efficiency residential refrigerators (0.85) and Introduction of CNG buses (0.75). Freight transport shift from road to railway and Cleaner cooking fuels had average values of progress indicators, 0.53 and 0.6, with respectively. The indicator values of the other tested mitigation options were all below 0.4 and hence greater efforts is needed to reach the mitigation targets.